The great unexpected - Creech, Sharon; local (New York : Joanna Cotler Books, 2012)
Orphans Naomi and Lizzie, living in America, and grown-up sisters Sybil and Nula, from Ireland, learn what life is truly about as they receive help from one another and open up their heart
Publisher's Weekly, July 2012
Kirkus Starred, May 2012
Booklist, June 2012
Horn Book, September 2012
s to love and forgiveness.
Follett Library Resources
Keywords: Follett Library Resources; sears -- Orphans; Juvenile fiction. -- Ireland; Juvenile fiction. -- Orphans; Fiction. -- Ireland; Fiction. -- Orphans; sears -- Ireland